New Zealand’s bibliometric record in research and development: 1990–2008 - Hendy, Shaun (New Zealand Science Review, 2010)
Over the last two decades, the New Zealand government has sought to achieve improved outcomes in science and technology through structural reform, rather than increased levels of investment in the sector. How successful has this strategy been? Here we look at New Zealand’s bibliometric output over the last two decades, using the Thompson Reuters Web of Science database. The database reveals that bibliometric productivity has remained static over this time period, with changes in publication rate driven by increasing levels of full–time equivalent staff members, principally through growth in the tertiary sector. Although the citation impact of university publications has increased, the citation impact of the Crown research institutes has grown at a similar, if not faster, rate, suggesting that the performance-based research fund is not responsible for this increase.